Exploring tourists’ virtual reality-based brand engagement: A uses-and-gratifications perspective - Raouf, A. R.; Hollebeek, L. D.; Loureiro, S. M. C.; Khan, I.; Hasan, R. (Journal of Travel Research, 2024)
Though prior research has addressed the role of virtual reality (VR) in tourism, the dynamics and consequences characterizing tourists’ VR-based brand engagement, which has grown significantly since the pandemic, remain tenuous, as, therefore, explored in this research. Addressing this gap, we develop and test a uses-and-gratifications-informed model that explores the impact of tourists’ VR involvement and VR identification on their VR-based brand engagement, and its ensuing effect on their VR-based brand cocreation and brand loyalty intent. Our empirical results corroborate the proposed associations, substantiating VR-based brand engagement’s mediating role. The analyses also confirm the moderating role of tourists’ technology readiness in the association of their VR-based brand engagement on the one hand, and VR-based brand cocreation and brand loyalty intent on the other (i.e., with more technology-ready individuals seeing stronger associations in this regard). We conclude by providing key implications for tourism research and practice.